Refleksi Teologis menggunakan Lingkaran Pastoral dalam Pendidikan Kristen - Yuwita Despriyantie; Hurman Hurman; Sarmauli Sarmauli (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
Christian Education is not only a medium for conveying religious knowledge but also a transformative process that shapes how students think, perceive life, and respond to God’s will. A recurring challenge is the gap between classroom teaching and students’ lived experiences, compounded by the erosion of teacher-student relationships. Recent incidents in Indonesia, including a teacher being reported to the police for advising students and students publicly humiliating a teacher, highlight a crisis in the moral and relational foundations of education. This study examines theological reflection through the pastoral circle as an approach to addressing this crisis by connecting faith with concrete life experiences. Using a qualitative literature study based on journals, theological books, and relevant news sources, the research finds that the stages of the pastoral circle—see, judge, act, and celebrate—provide a framework for interpreting experience through Scripture and guiding teachers in handling relational dilemmas with pastoral wisdom. This approach is important for restoring educational dignity and strengthening teacher-student relationships in the digital era.